Pengelolaan dan Pemanfaatan Media Sosial untuk Membangun Jiwa Kewirausahaan Siswa SMK - Hanifah, Ima Heni; Hidayati, Dian; Santoso, Achadi Budi; Widodo, Widodo (UMSU, 2024)
The purpose of this study was to determine the role of social media in fostering interest in entrepreneurship in class XI and XII students of SMK Muhammadiyah 4 Yogyakarta. The method used is a qualitative descriptive study where 10 informants who already have social media are interviewed using appropriate sampling and triangulation techniques. The results of the interviews show that social media has a very important role in increasing student interest in entrepreneurship, namely as a means of promotion and online sales exit points, where you do not have to meet directly with consumers. By using social networks, students do not need to spend a lot of money to rent an apartment and make flyers. However, students' interest or interest in entrepreneurship still needs to be improved and retrained. Because students feel less confident, less creative, do not have capital and do not dare to take the risk of loss in a company. The way to overcome this is to maximize their use of social media. If students have a lot of followers, then the products to be sold are likely to have many buyers. So that social media can increase student interest in entrepreneurship, especially classes XI and XII at SMK Muhammadiyah 4 Yogyakarta.